Analisis Kesehatan Lingkungan Sekolah Dasar pada Wilayah Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Febriyana, Vemi; Husin, Hasan (Avicenna: Jurnal Ilmiah, 2025)
Background School environmental health is an important factor in creating a healthy, safe, and comfortable learning atmosphere for students. This study aims to analyze the environmental health conditions at State Elementary School 88 South Bengkulu, located in the rural area of ​​Pino Raya District, South Bengkulu Regency. The general objective of this study is to determine the environmental health conditions in elementary schools in the Pino Raya District, South Bengkulu Regency. Specifically, this study aims to determine the provision of toilets, the availability and utilization of clean water, waste management, evaluation of wastewater disposal facilities, and students' perceptions of classroom conditions at SDN 88 South Bengkulu. The method used is descriptive qualitative with data collection techniques through in-depth interviews and observations. Informants consisted of fifth and sixth grade students, the principal, vice principal, class teachers, and cleaning staff. The results showed that students understand the importance of sanitation facilities such as toilets and clean water, but the available facilities do not meet health standards. There are problems with toilet cleanliness, clean water availability, waste management, wastewater disposal systems, and classroom ventilation and lighting, which affect student comfort and health. Infrastructure improvements and increased awareness of all school residents are needed. Conclusion: Based on research at SDN 88 Bengkulu Selatan, although students understand the importance of environmental cleanliness, various problems remain, such as substandard toilets, suboptimal clean water utilization, ineffective waste management, substandard wastewater treatment facilities (SPAL), and inadequate classrooms. Infrastructure improvements, ongoing education, and active participation from the school community are needed to create a healthy and appropriate learning environment. Keywords: Elementary School, Environmental Health